Discovery of a potent M5 antagonist with improved clearance profile. Part 2: Pyrrolidine amide-based antagonists. (15th December 2022) - Orsi, Douglas L.; Felts, Andrew S.; Rodriguez, Alice L.; Vinson, Paige N.; Cho, Hyekyung P.; Chang, Sichen; Blobaum, Anna L.; Niswender, Colleen M.; Conn, P. Jeffrey; Jones, Carrie K.; Lindsley, Craig W.; Han, Changho
Graphical abstract: Abstract: This Letter describes our ongoing effort to improve the clearance of selective M5 antagonists. Herein, we report the replacement of the previously disclosed piperidine amide (4, disclosed in Part 1) with a pyrrolidine amide core. Several compounds within this series provided good potency, subtype selectivity, and low to moderate clearance profiles. Interestingly, the left-hand side SAR for this series diverged from our earlier efforts.